Concepciones del Derecho y discrecionalidad judicial - Duque Sandoval, Oscar (2023)
It is necessary to adopt a concept of law that includes identifying criteria such as a variety of types of norms and the coexistence of formal aspects (related to powers and procedures laid down for the creation of law) and of material or content-based elements, set down in advance in terms of values and rights. This trait, with regard to legal interpretation, and especially to constitutional interpretation, assumes that the interpreterís decision, be it a lawmaker or a judge, must not only be valid but also correct, insofar as it must not contradict some material aspects that, although they refer to moral criteria, make up an essential part of the constitutive idea of the legal system in itself.